Electron microscopic findings of parallel tubular granules in a case of chronic neutrophilic leukaemia. - Takemori, N (1994)
A case of chronic neutrophilic leukaemia (CNL) is reported. The diagnosis was based on leucocytosis with mature neutrophils, a raised leucocyte alkaline phosphatase score, negative Philadelphia chromosome, and extensive infiltration of neutrophils in various differentiation stages into the bone marrow. When viewed by light microscopy, these neutrophils were almost normal in appearance, except for the presence of ring shaped nuclei and cytoplasmic vacuoles. Electron microscopy showed that neutrophilic promyelocytes and early myelocytes in the bone marrow frequently possessed unique rounded granules consisting of clustered parallel tubules, of 29-31 nm in diameter, and occasional amorphous electron dense material. These parallel tubules showed a hexagonal array; the granules were termed parallel tubular granules (PTGs). PTGs were positive for electron microscopic myeloperoxidase, and were seen exclusively in neutrophilic promyelocytes and early myelocytes. These findings suggest that PTGs represent certain primary granules peculiar to immature neutrophils. Their presence might also be helpful in diagnosing CNL.